Genesis of pyroxenite veins in supra-subduction zone peridotites: Evidence from petrography and mineral composition of Egiingol massif (Northern Mongolia) - Anas A. Karimov; Marina A. Gornova; Vasiliy A. Belyaev; Aleksander Ya. Medvedev; Nikolay V. Bryanskiy (China Geology, 2020)
ABSTRACT: Swarms of orthopyroxenite and websterite veins are found within Egiingol residual SSZ peridotite massif of Dzhida terrain (Central Asian Orogenic Belt, Northern Mongolia). The process of Egiingol pyroxenite veins formation is investigated using new major and trace element analyses of pyroxenite minerals, calculations of closure temperatures and composition of equilibrium melt. The pyroxenites show abundant petrographic and geochemical evidence for replacement of the residual peridotite minerals by ortho- and clinopyroxene due to melt-rock interaction. Relics of peridotite olivines are found in pyroxenites, Cr# of spinel increases from peridotites to pyroxenites, and compositions of ortho- and clinopyroxene change from peridotite to pyroxenite. The authors show that calculated equilibrium melts for investigated pyroxenites are very similar to compositions of boninite lavas from the Dzhida terrain. Therefore, formation of pyroxenite veins most likely resulted from percolation of boninite melts through the Egiingol peridotites. Orthopyroxenite veins formed at first, followed by websterite veins. Thus, the authors assume that pyroxenite veins represent the channels for boninitic melts migration in supra-subduction environment.